Urinary 5-HIAA Excretion is not Increased in Patients with Head and Neck Paragangliomas - Van Hulsteijn, Leonie T.; Van Duinen, Nicolette; Romijn, Johannes A.; Smit, Johannes W.A.; Corssmit, Eleonora P.M. (The International journal of biological markers, 2012)
Background Case reports have documented carcinoid-like features in head and neck paragangliomas (HNPGLs), which, in addition to catecholamine storing granules, may also contain granules with serotonin. Serotonin is metabolized to 5-hydroxyindoleacetic acid (5-HIAA). Aim To assess the urinary excretion rates of 5-HIAA and catecholamines in HNPGL patients. Methods In 114 consecutive HNPGL patients, normetanephrine, metanephrine, norepinephrine, epinephrine, VMA, dopamine, 3-methoxytyramine and 5-HIAA excretion rates were measured in two 24-hour urinary samples. Increased excretion rates were defined as an increase of the average hormone excretion rate of 2 urine samples above the reference range. In all patients with catecholamine excess, intrathoracic and abdominal paragangliomas were excluded by 123I-MIBG scintigraphy, MRI and/or CT. Genetic screening for mutations in genes of the succinate dehydrogenase (SDH) family was performed. Results Mean urinary 5-HIAA excretion rate was 14±9 μmol/24 hours (reference range 10–44 μmol/24 hours). Urinary 5-HIAA excretion was slightly increased in only 1 patient (48 μmol/24 hours). None of the 50 patients (44%) with increased urinary excretion rates of catecholamines and/or their metabolites had elevated 5-HIAA excretion. Conclusion Urinary 5-HIAA excretion is within the normal reference range in almost all HNPGL patients. Therefore, this parameter has no clinical relevance in the routine clinical assessment of HNPGL patients.